Maternal near miss: an Indian tertiary care centre audit - Samant, Padmaja Y.; Dhanawat, Juhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In practical terms, women are considered near-miss cases when they survive conditions which threaten their life i.e. organ dysfunction. Despite advances in medical science and increased awareness of measures for safe childbirth, unacceptably high maternal morbidity and mortality continues to plague developing countries like India. Our’s being a tertiary care centre, draws a lot number of high-risk patients and referrals. By auditing these near miss cases, we aim to identify the causes, factors leading to near miss, to identify management gaps to prevent near misses and maternal death. Methods: Retro-prospective cross-sectional study done over one and a half year. Patients were included based on the inclusion criteria. A questionnaire was used to evaluate the prospective cases and the indoor case sheets were used for retrospective cases. After data entry in excel sheet, data analysis was done using SPSS 21. Results were tabulated. Results: High number of Near Miss cases with preeclampsia being the commonest. Lack of proper facilities at the periphery health centers was the most common cause for referrals. Level 1 and level 2 delays were found in most cases. Conclusions: Timely referral, with adequate treatment at the peripheral hospitals will majorly reduce Near miss. Hence, proper development and functioning of peripheral hospitals are needed.